DESCRIPTION OF SARDINELLA DAYI REGAN (PISCES: CLUPEIDAE) OF INDIAN SEAS WITH REMARKS ON ITS CLOSE SIMILARITY WITH SARDINELLA MADERENSIS (LOWE) AND SARDINELLA WSSIEUI (VALENCIENNES) - Raja, B T Antony; Lazarus, S (Indian Journal of Fisheries, 2011)
Since the existing descriptions of Sardinella dayi Regan are based on veryfew specimens, a detailed account of its morphoihetric and meristic chanicters onthe basis of 50 specimens collected from Karwax (type locality), Vizhinjam and.Tuticorjn of- the Indian coast, is presented. It is concluded that the material fromMauritius figured and included by Fowler (1941) under 5. dayi is referable toS. jusyieui (Valenciennes). Drawing attention to the close similarity between thesetwo species and S. maderensis, it is recommended that future studies should assesshow far the differences between these species justify distinction at species level